Double‐Shelled Hollow SiO2@N‐C Nanofiber Boosts the Lithium Storage Performance of [PMo12O40]3−. Issue 53 (13th August 2021) - Hu, Hanbin; Yang, Yixin; Jiang, Xiao; Wang, Jiaxin; Cao, Dongwei; He, Lei; Chen, Wei; Song, Yu‐Fei
Abstract: Polyoxometalates (POMs)‐based materials, with high theoretical capacities and abundant reversible multi‐electron redox properties, are considered as promising candidates in lithium‐ion storage. However, the poor electronic conductivity, low specific surface area and high solubility in the electrolyte limited their practical applications. Herein, a double‐shelled hollow PMo12 −SiO2 @N−C nanofiber (PMo12 −SiO2 @N−C, where PMo12 is [PMo12 O40 ] 3−, N−C is nitrogen‐doped carbon) was fabricated for the first time by combining coaxial electrospinning technique, thermal treatment and electrostatic adsorption. As an anode material for LIBs, the PMo12 −SiO2 @N−C delivered an excellent specific capacity of 1641 mA h g −1 after 1000 cycles under 2 A g −1 . The excellent electrochemical performance benefited from the unique double‐shelled hollow structure of the material, in which the outermost N−C shell cannot only hinder the agglomeration of PMo12, but also improve its electronic conductivity. The SiO2 inner shell can efficiently avoid the loss of active components. The hollow structure can buffer the volume expansion and accelerate Li + diffusion during lithiation/delithiation process. Moreover, PMo12 can greatly reduce charge‐resistance and facilitate electron transfer of the entire composites, as evidenced by the EIS kinetics study and lithium‐ion diffusion analysis. This work paves the way for the fabrication of novel POM‐based LIBs anode materials with excellent lithium storage performance. Abstract : Excellent lithium storage was achieved by the double‐shelled hollow PMo12 −SiO2 @N−C nanocomposites. The outermost N−C shell can improve the electronic conductivity and promote the dispersion of PMo12 clusters. The SiO2 inner shell can efficiently avoid the loss of active components. The hollow structure can benefit a faster lithium‐ion kinetics by shorten lithium‐ion diffusion path and buffer volume expansion during lithiation/delithiation process. And PMo12, as an electron sponge, can greatly reduce charge‐resistance and accelerate electron transfer of the composite.